POTENSI PENGGUNAAN VIRTUAL REALITY DALAM PERSIAPAN PENCITRAAN MAGNETIC RESONANCE IMAGING (MRI) UNTUK MENGURANGI KECEMASAN PADA ANAK - Abdiman, I Made Tobias; Tanaji, Clara Meyly (Essence of Scientific Medical Journal; Vol 21 No 2 (2024): Volume 21 No. 2 (Juli - Desember 2023) Essential: Essence of Scientific Medical Journal, 2024)
Introduction: Magnetic Resonance Imaging (MRI) is essential for patients, including pediatric patients. However, these procedures often cause anxiety in children. Anxiety can have a negative impact on children's health and well-being. Therefore, there is a need for effective methods to reduce children's anxiety before and during medical imaging. This review summarizes studies related to the potential use of virtual reality (VR) as a method of anxiety management in children undergoing medical imaging. Discussion: Some studies show that VR can provide exposure and simulation related to MRI procedures that can help children understand and overcome their fear and uncertainty. VR can also provide immersive and interactive distraction through engaging and fun games. These studies show that VR can reduce children's anxiety levels before and during MRI, as well as increase children's satisfaction and engagement in the imaging process. Conclusion: VR has great potential in MRI preparation to reduce anxiety in children. VR can provide information, observation, modeling, and exposure that can increase children's knowledge and skills in dealing with MRI procedures. VR can also provide an effective and fun distraction that can distract children from the pain and discomfort that may arise during an MRI. VR can be an innovative and beneficial method to improve the quality of healthcare for children undergoing medical imaging.